Investigation lateral root development in Arabidopsis thaliana - Alsaffar, Nora (2023)
Root system architecture (RSA) is crucial for plant growth, nutrient and water uptake, and adaption to the environment. Lateral root (LR) is a crucial component of RSA to maximize the root surface area for acquiring soil resources. Therefore, understanding the molecular mechanisms regulating root traits such as lateral root development will be vital for future crop improvement programs and tackling global food insecurity. This study presents a comprehensive time-series transcriptome dataset generated using RNA sequencing technology (RNAseq) of Arabidopsis thaliana wild-type (Columbia; Col). This dataset corresponds to all developmental phases of LR, from the early stage of lateral root primordia (LRP) initiation to emerge from the primary root (PR). In total, 5,480 differentially expressed genes (DEGs), including 347 transcription factors (TFs) and 165 putative long non-coding RNA (lncRNA) transcripts, were detected across time points. In addition, a comparative analysis of four transcriptome datasets of the mutant of the key LR initiation regulators; AUXIN RESPONSE FACTOR (ARF) 7 and 19, Lateral ORGAN BOUNDARIES DOMAIN (LBD) 16 and 29. This research aims to identify protein-coding and non-coding candidates that have a potential role in LR development. Nineteen candidates that have not been previously linked to LR development exhibit a significant lateral root defect phenotype. This study focused mainly on the potential regulatory role of GATA8, BLH6, and AT5G47660 (Trihelix) and their targets as candidates for further genetic and molecular characterization. In the case of the noncoding candidates, two putative lincRNA (linc100 and linc229) showed a defect phenotype.